2018
DOI: 10.1371/journal.pone.0202901
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic supplements prevented oxonic acid-induced hyperuricemia and renal damage

Abstract: Hyperuricemia is highly prevalent and especially common in subjects with metabolic, cardiovascular and renal diseases. In chronic kidney disease, hyperuricemia is extremely common, and uric acid (UA) excretion relies on gut uricolysis by gut microbiota. Current therapy for lowering serum UA includes drugs that may produce undesired secondary effects. Therefore, this pilot study was designed to evaluate the potential of two probiotic supplements to reduce systemic uric acid concentrations. Secondary objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…Some studies have reported altered gut microbiome in gout patients (Shao et al, 2017), with gut bacteria expressing the gene of allantoinase significantly reduced (Crane, 2013), suggesting that altered gut microbiota may associate with gout, and therefore, may help distinguish gout patients from healthy patients and serve as new targets for disease treatment (Guo et al, 2016). As reported previously, certain probiotics containing uricolytic ability can be used to help prevent oxonic acid-induced hyperuricemia in animals (García-Arroyo et al, 2018). Similarly, a potential probiotic has been found that improves fructose-induced hyperuricemia by reducing intestinal inosine (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 82%
“…Some studies have reported altered gut microbiome in gout patients (Shao et al, 2017), with gut bacteria expressing the gene of allantoinase significantly reduced (Crane, 2013), suggesting that altered gut microbiota may associate with gout, and therefore, may help distinguish gout patients from healthy patients and serve as new targets for disease treatment (Guo et al, 2016). As reported previously, certain probiotics containing uricolytic ability can be used to help prevent oxonic acid-induced hyperuricemia in animals (García-Arroyo et al, 2018). Similarly, a potential probiotic has been found that improves fructose-induced hyperuricemia by reducing intestinal inosine (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 82%
“…118 Additionally, probiotic-containing diet prevents hyperuricemia induced by oxonic acid, which is essential for normal blood pressure and renal function. 119 Alternatively, the use of urate-lowering drugs on rats with hyperuricemia causes changes in the composition of microbiota indicating the effective treatment of hyperuricemia. 120…”
Section: The Role Of Microbiota In the Pathophysiology Of Obesitymentioning
confidence: 99%
“…Recently, studies on mice have shown that probiotics could reveal to be an additional therapeutic option. Lactobacillus strains have shown to lower SUA with beneficial effects on hypertension and renal disease [26,27].…”
Section: Diet and Lifestylementioning
confidence: 99%